Analisis Kemampuan Visual Spasial Siswa dalam Menyelesaikan Soal Geometri tentang Kubus dan Balok Ditinjau dari Jenis Kelamin - Nurainun, Nurainun; Sukayasa, Sukayasa; Ismaimuza, Dasa; Meinarni, Welli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to obtain the results of an analysis of the visual spatial abilities of class IX MTs DDI Ogoamas students in solving geometry questions about cubes and blocks in terms of gender. This research uses a qualitative method with qualitative descriptive. The subjects of this research were 2 students out of 28 class IX students, namely female students and male students. Data was collected using written tests and interviews. The results of this study showed that the female subject (AR) was able to imagine or describe a block composed of several cubes, then the subject was also able to determine the length, width and height of the block based on the length of the edge of the cube, but the subject was not able to solve the problem correctly because he made a mistake in using the block volume formula, the subject was also unable to determine the pattern of the three cubes known from the problem. The male subject (AD) was able to imagine or describe a block composed of several cubes, then the subject was also able to determine the length, width and height of the block based on the length of the edge of the cube. The subject is able to solve the problem of determining the volume of the block correctly, the subject is also able to determine the pattern of the three cubes so that he is able to determine the volume of the next cube. The conclusion of this research is that the visual spatial abilities of male students are better than female students. Keywords: Spatial Visual Ability, Cubes and Blocks, Gender